Exploring the critical care nurses' experiences regarding moonlighting - BR Bhengu (AOSIS, 2001)
While moonlighting is so prevalent amongst critical care nurses, there are no documented facts in this country about how it affects the nurses and the hospital management, considering the nature of their work that is both physically, mentally and emotionally strenuous. The aim of this study was to explore the critical care nurses' rationale and experiences regarding holding a second job (moonlighting). A non-experimental exploratory study was done using focus groups. Many positive and less positive experiences were revealed, for example, economical, educational, and psychosocial ones. Participatory control of moonlighting activity was suggested involving both management and staff at functional level.